Developing bilingual readers' reading strategies using educational drama methodologies: an experimental study - Μαστροθανάσης, Κωνσταντίνος; Κλαδάκη, Μαρία; Βάσιου, Αικατερίνη (Education Sciences, 2024)
The aim of this experimental study is to investigate the impact of drama-based instruction on the development of reading strategies used by bilingual student populations. The research design included pre-measurement of the reading strategies of two control groups and one experimental group of 388 total emergent bilingual students using a standardized scale, drama-based interventions lasting seven weeks, and post-measurement of reading strategies. The results of the study showed that reader's theatre and storytelling theatre were successful methods for developing bilingual students' strategic thinking on reading and showed large effect sizes and statistically significant differences in the use of cognitive, metacognitive, social, and affective strategies. The findings support the hypothesis that drama-based instruction can influence bilingual readers' reading strategies and improve their use, especially in terms of metacognitive development.